ANALISIS LABA PERDAGANGAN HARIAN PADA VALUTA ASING MENGGUNAKAN INDIKATOR MOVING AVERAGE CONVERGENCE DIVERGENCE (MACD) DAN FULL STOCHASTIC OSCILLATOR - , Khaerul Fikhi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The major purposes of this study are to compare profit generated by Moving Average Convergence Divergence (MACD) indicator with Full Stochastic Oscillator (FSO) indicator if used as a single indicator in forex day trading and also to compare profit generated by MACD single indicator and FSO single indicator with MACD and FSO combined indicators in forex day trading. The data used in this study are profit that were calculated based on buy and sell signal from MACD indicator, FSO indicator and combined indicators MACD and FSO in 5 minutes, 15 minutes, 30 minutes and 60 minutes time frames. Profit that was calculated based on price provided by FBS broker used Metatrader4 program. Currency pairs that used are EURO/USD, USD/JPY and GBP/USD. This study shows for day trading FSO is more optimal in generating profit than MACD as a single indicator and combined indicators MACD and FSO are more optimal in generating profit than MACD single indicator and FSO single indicator.